A Running Start: Resource Guide for Youth Running Programs. Issue 2 (12th February 2016) - Jenny, Seth; Becker, Andrew; Armstrong, Tess
Abstract : The lack of physical activity is an epidemic problem among American youth today. In order to combat this, many schools are incorporating youth running programs as a part of their comprehensive school physical activity programs. These youth running programs are being implemented before or after school, at school during recess at the elementary level, or as a community physical activity program at both the primary and secondary levels. This article highlights 13 nationwide youth running programs and 19 additional programs offered in geographic-specific locations within the United States. Moreover, many adult marathon races now provide a simple "Kid's Marathon" mileage training plan so that youth can try to accumulate 25 (or 25.2) miles in the weeks leading up to the race so they can then run their final 1.2 (or 1) mile at a youth race in conjunction with the marathon. A sampling of marathons that offer training plans prior to a youth race, as well as additional marathons offering youth races, is also provided.